2018
DOI: 10.1002/stem.2906
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Airway Epithelial Tissue Stem Cell Differentiation by β-Catenin, P300, and CBP

Abstract: The wingless/integrase-1 (WNT)/β-catenin signaling pathway is active in several chronic lung diseases including idiopathic pulmonary fibrosis, asthma, and chronic obstructive pulmonary disease. Although this WNT/β-catenin pathway activity is associated with an increase in mucus cell frequency and a decrease in ciliated cell frequency, a cause and consequence relationship between signaling and cell frequency has not been established. We previously demonstrated that genetic stabilization of β-catenin inhibited d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 47 publications
1
50
1
Order By: Relevance
“…Wnt/β-catenin signaling functions in mucociliary epithelia, but results from manipulations often appear contradictory as to the exact roles Wnt signaling plays in different cell types and processes. Wnt/β-catenin was suggested to promote MCC specification and expression of FOXJ1 , a key transcription factor in motile cilia formation (Hou et al, 2019; Huang and Niehrs, 2014; Malleske et al, 2018; Stubbs et al, 2008; Walentek et al, 2012, 2015). In contrast, Wnt/β-catenin activation can also lead to loss of MCCs or Goblet secretory cell hyperplasia (Hashimoto et al, 2012; Mucenski et al, 2005; Reynolds et al, 2008; Schmid et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β-catenin signaling functions in mucociliary epithelia, but results from manipulations often appear contradictory as to the exact roles Wnt signaling plays in different cell types and processes. Wnt/β-catenin was suggested to promote MCC specification and expression of FOXJ1 , a key transcription factor in motile cilia formation (Hou et al, 2019; Huang and Niehrs, 2014; Malleske et al, 2018; Stubbs et al, 2008; Walentek et al, 2012, 2015). In contrast, Wnt/β-catenin activation can also lead to loss of MCCs or Goblet secretory cell hyperplasia (Hashimoto et al, 2012; Mucenski et al, 2005; Reynolds et al, 2008; Schmid et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In MCCs, we have observed a specific expression of both members from the Reptin family which are ATP-dependent DNA helicases that have been identified as Wnt signaling repressors [63,64]. As Reynolds and colleagues recently showed that β-catenin was necessary for mucus and ciliated cell specification [57], additional investigations should certainly be carried out to characterize precisely the role of Wnt/β-catenin during airway epithelial regeneration.…”
Section: Discussionmentioning
confidence: 86%
“…For instance, in the hair follicle precortex, βcatenin stimulates Notch signaling by inducing Jag1 transcription [56]. In the context of airway epithelium, a very recent study demonstrated that β-catenin signaling is required for the early stages of mucus and ciliated cell differentiation, which they defined as "specification", but was detrimental to the later "commitment" stages [57]. Wnt also seems to be related to epithelial remodeling upon inflammatory situations: Ordovas-Montanes and colleagues have recently shown that in nasal polyps, which are characterized by an inflammatory state favoring GCs at the expense of MCCs, there is an altered balance between Wnt and Notch signaling, in favor of Wnt signaling [30].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies unveiled that b-catenin is dispensable in the bronchiolar airways for homeostasis and injury repair (Zemke et al, 2009), while others affirmed that it may play a role in specification of mucus and ciliated cells in vitro (Malleske et al, 2018). In the proximal airway, we find that medium levels of Wnt/b-catenin signaling promote differentiation to the ciliated cell fate, consistent with work of others that has molecularly dissected a role for Wnt/ b-catenin in regulating Foxj1-driven ciliogenesis across several species (Caron et al, 2012;Walentek et al, 2012Walentek et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%